High‐impact hydrologic events and atmospheric rivers in California: An investigation using the NCEI Storm Events Database - Allison M. Young; Klint T. Skelly; Jason M. Cordeira (Geophysical Research Letters)
Abstract Atmospheric rivers (ARs) are long, narrow corridors of enhanced integrated water vapor and integrated vapor transport that can result in high‐impact hydrologic events (HIHEs) including floods, flash floods, and debris flows. This study examined the relationship between HIHEs and ARs in California for 10 water years by using the National Centers for Environmental Information Storm Events Database and a catalog of landfalling ARs provided by Rutz et al. (). Results illustrated that HIHEs related to floods and debris flows are commonly associated with ARs during the cold season across Northern California, whereas HIHEs related to flash floods are commonly not associated with ARs during the warm season across Southern California. Composite analyses illustrated that HIHEs associated with landfalling ARs are associated with synoptic‐scale flow patterns that support southwesterly water vapor flux that aligns favorably with California coastal topography to maximize upslope flow and orographic precipitation.